2013
DOI: 10.1002/ps.3618
|View full text |Cite|
|
Sign up to set email alerts
|

Population and damage projection of Spodoptera litura (F.) on peanuts (Arachis hypogaea L.) under different conditions using the age‐stage, two‐sex life table

Abstract: Population projections based on life tables and stage-specific consumption rates can reveal the stage structure and damage potential of the pest population. Our results showed that monitoring data obtained by using pheromone traps were not in concordance with the damage potential of the pest population. This approach offers a promising tool for pest management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
129
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 309 publications
(142 citation statements)
references
References 28 publications
2
129
0
Order By: Relevance
“…The growth of M. dirhodum population liberated from diseases, predation and parasitism was projected for each treatment based on the life table data using the program TIMING-MSChart54 and the approach described in Chi55 and Tuan et al 56…”
Section: Methodsmentioning
confidence: 99%
“…The growth of M. dirhodum population liberated from diseases, predation and parasitism was projected for each treatment based on the life table data using the program TIMING-MSChart54 and the approach described in Chi55 and Tuan et al 56…”
Section: Methodsmentioning
confidence: 99%
“…A similar phenomenon has been found in other insects: Reddy and Chi (2015) noted that sweetpotato weevils reared on a normal host ( Ipomoea batatas ) have a lower peak reproductive value than those reared on an alternative host; while Saska et al (2016) found that the highest age-stage reproductive value was estimated to occur in offspring of Metopolophium dirhodum reared under a high concentration of glyphosate-based herbicide treatments. Since the v xj is calculated using only s xj and f xj (Huang and Chi 2011, Tuan et al 2014b), the high reproductive value but low fecundity may be due to the high s xj value found in C. nipponensis during short photoperiods.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al (2013) and Tuan et al (2014b) demonstrated the usefulness of population projection and pest damage prediction using life tables in biological control projects. In our study, population projection was conducted for a test population response under unfavorable conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The development and survivorship of insects are usually measured by the Life-spans. Life-spans summarize the survival and reproductive potential of insect population on different host and under various environmental conditions (Akköprü, Atlıhan, Okut, & Chi, 2015;Tuan, Lee, & Chi, 2014;Yang et al, 2015). Suitable host plant gives short life spans and high survival rates (Schowalter, 2016).…”
Section: Introductionmentioning
confidence: 99%